Le postille manzoniane al 'Dictionnaire des proverbes français' di Pierre de la Mésangère (Prassi Ecdotiche della Modernità Letteraria, 2018)
Il contributo propone la presentazione e il commento di una selezione delle postille manzoniane al Dictionnaire des proverbes français di Pierre de la Mésangère (1823). Si tratta di postille di natura linguistica in quanto Manzoni, appoggiandosi ancora a francese e milanese, cerca, con l’aiuto della Crusca, di trovare l’equivalente italiano (o meglio, toscano) dei proverbi postillati. La postillatura del volume, per quanto interrotta a metà circa, rappresenta una preziosa testimonianza della precoce consapevolezza manzoniana dei segmenti di lingua da indagare per il romanzo: il confronto delle postille con la cosiddetta Seconda minuta (Gli sposi promessi) dimostra infatti che molti dei proverbi postillati trovano accoglienza proprio in questa fase redazionale. Manzoni's annotations on Pierre de la Mésangère's 'Dictionnaire des proverbes français'This article aims at describing and commenting a selection of Manzoni’s marginalia to Pierre de la Mésangère’s Dictionnaire des proverbes français (1823). The typology of these marginalia can be defined linguistic since Manzoni, still relying on French and the Milanese dialect, tries, thanks to the Crusca Vocabulary as well, to find a proper Italian (or better, Tuscan) translation of the French proverbs. The annotation of the volume, despite being half done, proves to be a valuable evidence of Manzoni’s early awareness towards the most suitable linguistic elements for his novel: as a matter of fact, the comparison between these marginalia and the different drafts of the novel shows that many of the annotated proverbs are reused in the so-called Seconda minuta.
Keywords: Manzoni; postille; Seconda minuta; Pierre de la Mésangère; Dictionnaire des proverbes français